Endophytic fungi: a tool for plant growth promotion and sustainable agriculture - Baron, Noemi Carla [UNESP]; Rigobelo, Everlon Cid [UNESP] (Taylor & Francis, 2022)
Endophytic fungi are found in most, if not all, plant species on the planet. They colonise inner plant tissues without causing symptoms of disease, thus providing benefits to the host plant while also benefiting from this interaction. The global concern for the development of more sustainable agriculture has increased in recent years, and research has been performed to decipher ecology and explore the potential of endophytic interactions in plant growth. To date, many studies point to the positive aspects of endophytic colonisation, and in this review, such research is summarised based on the direct (acquisition of nutrients and phytohormone production) and indirect (induced resistance, production of antibiotics and secondary metabolites, production of siderophores and protection for abiotic and biotic stresses) benefits of endophytic colonisation. An in-depth discussion of the mechanisms is also presented.
Keywords: Biocontrol; Biofertilization; Endophytic fungi; Plant growth; Sustainable agriculture